2018
DOI: 10.1002/eat.22942
|View full text |Cite
|
Sign up to set email alerts
|

Improving decision‐making and cognitive impulse control in bulimia nervosa by rTMS: An ancillary randomized controlled study

Abstract: Objective Impaired decision‐making and inhibitory control may be involved in the pathophysiology of psychiatric disorders like bulimia nervosa (BN). Their improvement after neuromodulation may underpin clinical improvement. We assessed the effects of rTMS on these cognitive functions in a sample of women with BN. Methods Thirty‐nine participants (22 in a sham group and 17 in an rTMS group) were assessed before and after 10 high frequency rTMS sessions over the left dorsolateral prefrontal cortex (DLPFC). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…The results showed a decrease in food craving, and in some studies a reduction in food binging or purging behavior (for review see Dalton et al [44]). DLPFC stimulation may also improve the inhibitory control and decision making in patients with BN [43]. A study on the correlation between salivary cortisol and rTMS on the left DLPFC in BN showed that salivary cortisol concentrations were significantly lower in the rTMS arm compared with the sham rTMS arm.…”
Section: Bulimia Nervosa and Binge-eating Disordermentioning
confidence: 99%
“…The results showed a decrease in food craving, and in some studies a reduction in food binging or purging behavior (for review see Dalton et al [44]). DLPFC stimulation may also improve the inhibitory control and decision making in patients with BN [43]. A study on the correlation between salivary cortisol and rTMS on the left DLPFC in BN showed that salivary cortisol concentrations were significantly lower in the rTMS arm compared with the sham rTMS arm.…”
Section: Bulimia Nervosa and Binge-eating Disordermentioning
confidence: 99%
“…Dabei handelt es sich vorwiegend um Studien, die in den letzten 5 Jahren publiziert wurden; 3 Studien bei AN [13][14][15], 4 bei BN [16][17][18][19], eine bei BES [20] und eine bei verschiedenen ES [21]. 4 Studien verwendeten tDCS [15,17,20,21], 5 Studien rTMS [13,14,16,18,19]. Die 9 Artikel wurden thematisch anhand der verfolgten Behandlungsziele in 3 verschiedene Bereiche eingeteilt, die im Folgenden dargestellt werden.…”
Section: Die Anwendung Von Nihs Bei Esunclassified
“…Steigerung der Selbstkontrolle zur Reduktion des Verlangens nach Nahrung und der NahrungsaufnahmeDie meisten Studien, die NIHS bei ES einsetzten, konzentrieren sich auf den dorsolateralen präfrontalen Kortex (DLPFC), um die Selbstkontrolle bei Patienten zu erhöhen und so das Verlangen nach Nahrung und die Nahrungsaufnahme zu reduzieren[16][17][18][19][20]. Dies sind wichtige Schritte bei der Behandlung von Essanfällen.In einer Studie[16] wurden 38 Patienten mit BN in einer Sitzung mit hochfrequenter rTMS am linken DLPFC stimuliert.…”
unclassified
See 1 more Smart Citation
“…The first article, written by Smith, Mason, Johnson, Lavender, and Wonderlich (2018), provides a helpful overview of past literature on neurocognitive dysfunction in people with EDs, as well as novel directions for future research and treatment (Smith et al, 2018). In the second article, Guillaume et al (2018) presents findings from a study that used 2 weeks of high frequency repeated transcranial magnetic stimulation of the dorsolateral prefrontal cortex in women with bulimia nervosa to see if this treatment would lead to changes in a specific neurocognitive biomarker for bulimia nervosa (Guillaume et al, 2018). Finally, we selected an article by Feusner, Deshpande, and Strober (2017), which proposes a new explanation for why people with anorexia nervosa have difficulty perceiving their body size accurately, as well as suggestions for future brain-based research designed to normalize body-size misperception (Feusner et al, 2017).…”
Section: Hitting the Bullseye: The Role Of Experimental Therapeuticmentioning
confidence: 99%